Penguatan Deteksi Dini Tuberkulosis Melalui Program BERSIH TB: “Bersama Santri dalam Edukasi dan Skrining TB” - Sary, Annisa Novita; Oktariyani Dasril; Sandra Hardini (Lembaga Pengembangan Kinerja Dosen, 2025)
Tuberculosis (TB) remains a major health problem in Indonesia, particularly in Islamic boarding schools (pesantren) where overcrowding and low awareness increase transmission risks. This community engagement aimed to improve knowledge, early detection, and reduce TB stigma at SMA Dar El Iman Islamic Boarding School, Padang. A participatory approach was conducted from July to September 2025 involving 34 female students. Activities included health education, student cadre formation through the Red Cross Youth (PMR), TB symptom screening, and anti-stigma campaigns. Results showed students’ knowledge improved from 45% to 90%, five student cadres were established as peer educators, and three suspected TB cases were referred to health facilities. Evaluation indicated increased awareness of dormitory hygiene, ventilation, and peer support. This program highlights pesantren as a strategic platform for TB prevention and early detection. In conclusion, school-based TB education and screening effectively enhance students’ capacity and support the national TB elimination target by 2030.